Plasmodium chabaudi-Infected Erythrocytes Adhere to CD36 and Bind to Microvascular Endothelial Cells in an Organ-Specific Way - Mota, Maria M. (American Society for Microbiology, 2000)
Adherence of erythrocytes infected with Plasmodium falciparum to microvascular endothelial cells (sequestration) is considered to play an important role in parasite virulence and pathogenesis. However, the real importance of sequestration for infection and disease has never been fully assessed. The absence of an appropriate in vivo model for sequestration has been a major barrier. We have examined the rodent malaria parasite Plasmodium chabaudi chabaudi AS in mice as a potential model. Erythrocytes infected with this parasite adhere in vitro to purified CD36, a critical endothelium receptor for binding P. falciparum-infected erythrocytes. P. c. chabaudi-infected erythrocytes adhere in vitro to endothelial cells in a gamma interferon-dependent manner, suggesting the involvement of additional adhesion molecules in the binding process, as is also the case with P. falciparum-infected cells. Furthermore, plasma or sera from infected and hyperimmune mice, respectively, have the ability to block binding of infected erythrocytes to endothelial cells. In vivo, erythrocytes containing mature P. c. chabaudi parasites are sequestered from the peripheral circulation. Sequestration is organ specific, occurring primarily in the liver, although intimate contact between infected erythrocytes and endothelial cells is also observed in the spleen and brain. The results are discussed in the context of the use of this model to study (i) the relationship between endothelial cell activation and the level of sequestration and (ii) the primary function of sequestration in malaria infection.